Food and Nutritional Security Through Root and Tuber Crops Interventions-Impact Assessment in Tribal Regions of India - Nedunchezhiyan, M; Misra, R.S.; Ray, R.C.; Mukherjee, A; Laxminarayana, K; Rao, K.R.; Pati, K (JOURNAL OF ROOT CROPS, 2015)
Root and tuber crops are the one of the oldest group of crops domesticated by the human being. Nutritionally, they are on par with new world food crops. Greater yam (Dioscorea alata) and cassava (Manihot esculenta) are highly drought tolerant crops. Sweet potato (Ipomoea batatas) and yam bean (Pachyrrhizus erosus) can be grown in marginal soils. Under Tribal Sub Plan programme, yam, taro (Colocasia esculenta), sweet potato, yam bean and cassava cultivation was demonstrated in the tribal areas of Odisha, Chhatisgarh and Jharkhand states of India during 2012-13 for livelihood improvement and income generation. Greater yam 7400 kg, taro 1550 kg, yam bean 100 kg sweet potato 110000 vine cuttings and cassava 40000 sett were distributed to the tribal farmers and the area covered in all the three states together was greater yam 3.7 ha, taro 1.24 ha, yam bean 8.0 ha, sweet potato 2.2 ha and cassava 4.0 ha. Greater yam recorded higher yield of 458 kg 200 m-2 with the net return of Rs 4380. The net returns from yam and taro were higher than other crops implying their commercial stature. However, Benefit cost ratio from yam bean (2.76) was as high as greater yam (2.76). High yield and returns from the improved varieties of tuber crops increased the food availability in the household. Voluntary intake of available nutrient rich tubers improved the nutritional security of the disadvantaged tribal farmers in the above states.